2007
DOI: 10.1080/00207450600773459
|View full text |Cite
|
Sign up to set email alerts
|

Early Social Isolation Decreases the Expression of Calbindin D-28k and Dendritic Branching in the Medial Prefrontal Cortex of the Rat

Abstract: Social isolation in rodents is the most well characterized animal model for early stressful experiences and their neurobehavioral consequences. The present study analyzed the effects of early social isolation on the expression of the calcium binding protein calbindin-D28k (CAD) and dendritic arborization in the medial prefrontal cortex (mPFC) of the rat. Sprague-Dawley male rats were reared either under isolation or social conditions from 21 to 51 postnatal days. At the end of this period the animals were beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 42 publications
1
17
1
1
Order By: Relevance
“…For the basilar dendrites of mPFC neurons in the isolationreared rats, reduced arborization was revealed by the reduction of segment number especially in the third and fourth orders (Fig. 5d), in line with a previous report (Pascual et al 2007). Like the apical dendrites, the length of terminal segments of basilar dendrites also altered in the isolated rats (Fig.…”
Section: Dopamine Neurons In the Midbrainsupporting
confidence: 87%
“…For the basilar dendrites of mPFC neurons in the isolationreared rats, reduced arborization was revealed by the reduction of segment number especially in the third and fourth orders (Fig. 5d), in line with a previous report (Pascual et al 2007). Like the apical dendrites, the length of terminal segments of basilar dendrites also altered in the isolated rats (Fig.…”
Section: Dopamine Neurons In the Midbrainsupporting
confidence: 87%
“…REST-controlled miRNAs (e.g., Mir132, -124) are already known to regulate neuronal morphogenesis, differentiation, and synaptic plasticity (Vo et al, 2005;Conaco et al, 2006;Rajasethupathy et al, 2009). It is interesting to note that early life stress results in a decrease in dendritic length (Pascual et al, 2007), a decrease in the number of astrocytes (Musholt et al, 2009), abnormally high synaptic density (Ovtscharoff and Braun, 2001), and an attenuated basal neuronal activity (Stevenson et al, 2008) within the mPFC. More recently, Goodfellow et al (2009) reported an increased 5-HT1A-mediated outward current and an increased expression of 5htr1a mRNA in the mPFC during postnatal development of maternally separated rats, the latter of which was replicated by our present expression analyses.…”
Section: Role Of Mpfc In the Development Of Stress Vulnerabilitymentioning
confidence: 99%
“…Early postnatal life is a critical period for the development of the mPFC (Benes et al, 2000). Several lines of evidence show that early life stress results in abnormally high synaptic density (Ovtscharoff and Braun, 2001), decreased dendritic length (Pascual et al, 2007), attenuated basal neuronal activity (Stevenson et al, 2008), and increased serotonin (5-HT) 1A receptor-mediated outward currents during postnatal development (Goodfellow et al, 2009) within the mPFC. To date however, the molecular mechanisms underlying these plastic changes in the mPFC remain to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted that rearing rodents under deprivation of natural environmental stimulation causes severe impacts in the maturation of the prefrontal cortex-spanning from receptors (Melendez et al, 2004;Gregory and Szumlinski, 2008) and transmitters (Winterfeld et al, 1998;Brummelte et al, 2007) over structural alterations (Bagorda et al, 2006;Pascual et al, 2007;Fone and Porkess, 2008) to behavioural consequences (Winterfeld et al, 1998;Fone and Porkess, 2008;Gregory and Szumlinski, 2008)-as well as neurochemical changes in the limbic system (Busche et al, 2004;Galani et al, 2007;Fone and Porkess, 2008). Since the prefrontal cortex is reciprocally connected to the dentate gyrus via the entorhinal cortex, it might be reasonable that the imbalance between prefrontal and limbic activities also impacts the regulation of cell proliferation, differentiation and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Especially in the phase after weaning, when an individual begins to independently interact with its social and physical environment, the maturation of relevant brain areas is under considerable influence of external factors. Deprivation or impoverishment of the necessary social and physical stimulation can lead to differences in behavioural and neuroplastic development especially in the prefrontal-limbic system (Winterfeld et al, 1998;Busche et al, 2004;Melendez et al, 2004;Bagorda et al, 2006;Brummelte et al, 2007;Galani et al, 2007;Pascual et al, 2007;Fone and Porkess, 2008). These impacts even seem to refer to adult neurogenesis in the hippocampal dentate gyrus, although the results remain contradictory: in gerbils, socially and physically deprived rearing increased rates of hippocampal cell proliferation in adulthood (Keller et al, 2000).…”
Section: Introductionmentioning
confidence: 92%